TINDAK TUTUR ILOKUSI DALAM ARTIKEL RUBRIK NASIONAL DI KOMPAS: TELAAH ATAS RENCANA PENGOSONGAN KOLOM AGAMA DI KTP - M Khoirunnada (Wanastra: Jurnal Bahasa dan Sastra, 2016)
This article purposed to describe illocutionary speech acts (assertive/representative, directive, and commissive) appeared in some articles that discuss an issue about blanking out a religious column in Citizenzenship Identity Card. The theory used in this research is Austin’s speech acts theory then specified to Searle’s illocutionary theory. The method used is analytical descriptive qualitative based on data information. Finally, this research ended by finding types of illocutionary speech acts such as assertive/representative (stating and complaining), directive (advising and requesting—impositive), and commissive (promising) while for the expressive and declarations illocutionary are not found.Keywords: illocutionary speech acts (assertive/representative, directive, commissive, expressive and declarations)